Probing non-locality of interactions in a Bose–Einstein condensate using solitons. (22nd October 2018) - Pendse, Abhijit; Bhattacharyay, A
Abstract: We consider a Bose–Einstein condensate (BEC) with non-local inter-particle interactions. The local Gross–Pitaevskii (GP) equation is valid for the gas parameter, but for, the BEC is described by a modified GP equation (MGPE). We study the exact solutions of the MGPE describing bright and dark solitons. It turns out that the width of these non-local solitons has qualitatively similar behaviour as the modified healing length due to the non-local interactions of the MGPE. We also study the effect of the non-locality and gas parameter ( ν ) on the stability of the solitons using the Vakhitov–Kolokolov (VK) stability criterion. We show that these soliton solutions are stable according to the VK criterion. Further, the stability of these soliton solutions gets enhanced due to the non-locality of interactions.